Quantitative evaluation of drug or device effects on ventricular remodeling as predictors of therapeutic effects on mortality in patients with heart failure and reduced ejection fraction: a meta-analytic approach - Kramer, Daniel G; Trikalinos, Thomas A; Kent, David M; Antonopoulos, George V; Konstam, Marvin A; Udelson, James E (Journal of the American College of Cardiology, 2010)
The purpose of this study was to quantitatively assess the relationship between therapy-induced changes in left ventricular (LV) remodeling and longer-term outcomes in patients with left ventricular dysfunction (LVD). Whether therapy-induced changes in left ventricular ejection fraction (LVEF), end-diastolic volume (EDV), and end-systolic volume (ESV) are predictors of mortality in patients with LVD is not established. Searches for randomized controlled trials (RCTs) were conducted to identify drug or device therapies for which an effect on mortality in patients with LVD was studied in at least 1 RCT of > or = 500 patients (mortality trials). Then, all RCTs involving those therapies were identified in patients with LVD that described changes in LVEF and/or volumes over time (remodeling trials). We examined whether the magnitude of remodeling effects is associated with the odds ratios for death across all therapies or associated with whether the odds ratio for mortality was favorable, neutral, or adverse (i.e., statistically significantly decreased, nonsignificant, or statistically significantly increased odds for mortality, respectively). Included were 30 mortality trials of 25 drug/device therapies (n = 69,766 patients; median follow-up 17 months) and 88 remodeling trials of the same therapies (n = 19,921 patients; median follow-up 6 months). The odds ratio for death in the mortality trials was correlated with drug/device effects on LVEF (r = -0.51, p < 0.001), EDV (r = 0.44, p = 0.002), and ESV (r = 0.48, p = 0.002). In (ordinal) logistic regressions, the odds for neutral or favorable effects in the mortality RCTs increased with mean increases in LVEF and with mean decreases in EDV and ESV in the remodeling trials. In patients with LVD, short-term trial-level therapeutic effects of a drug or device on LV remodeling are associated with longer-term trial-level effects on mortality.